Uniform estimates of integral strong average derivations of continuous functions by integral functions - Pachulia , N. L. (Ukrains’kyi Matematychnyi Zhurnal, 2025)
Estimates for the (λ, φ)-integral strong mean deviations of continuous functions on the whole axis by entire functions of finite degree are obtained.